Iodination of terminal alkynes using KI/CuSO4 – A facile method with potential for radio-iodination - Ferris,T; Carroll,L; Mease,RC; Spivey,AC; Aboagye,EO (Tetrahedron Letters, 2019)
Herein, we report an efficient new method for the iodination of terminal alkynes using stoichiometric KI and CuSO4 in a mix of acetonitrile and acetate buffer that holds promise for further development into a method for radio-iodination.